Washington Paper - Filling and Blowing-In at the Durham Blast-Furnace - B. F. Fackenthal (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1890)
One of the practical questions presented to the blast-furnace manager, with regard to which little help can be obtained from existing technical literature, is the manner of filling and blowing-in. This operation is often performed according, more or less, to traditions which have come down from earlier practice, and which, if not positively detrimental when followed with the large modern furnace, may at least be greatly improved, just as the running of the furnace itself, while in blast, has been improved. It is not necessary, as many of the old furnace-men believed, to make a lot of white or silver-gray iron at the start, or to spend many weeks, or months even, in bringing the furnace to its normal burden. It has seemed to me that the publication of carefully-recorded data of practice on this point may be interesting to the members of the Institute engaged in the management of blast-furnaces. The enlarged blast-furnace at the Durham Iron Works, Riegelsville, Pa., owned by Messrs. Cooper & Hewitt, of New York City, was first put in blast February 21, 1876, since which time it has made seven blasts, and is now running on the eighth. A description of the furnace-plant, together with a record of the fifth blast, was given in my paper read at the Chattanooga meeting, May, 1885 (Transactions, xiv., 130). After some of the early blasts the furnace-lines underwent considerable change, and I have thought best to accompany this paper with drawings showing the lines and the tuyere-arrangement (see Plates I. and II.), and to give also the following summary of the conditions and results of each blast. During the first and second blasts no coke was used, and the furnace ran very irregularly, showing a constant tendency to scaffold, which was attributed, in great part, to the small hearth and other defective lines. The large proportion of air required at this furnace is accounted for by the fact that the engines are defective, and do not deliver into the furnace the amount of air indicated by the pistondisplacement.